Oxford handbook of musculoskeletal nursing - Oliver, Susan M. (Oxford : Oxford University Press, 2020)
Filled with practical advice and up-to-date clinical information and management techniques, this text is an invaluable guide for all nurses and allied health professionals working with patients who have musculoskeletal conditions. Features new chapters on the patient's perspective, nurse-led clinics, and public health awareness.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 24, 2020).
Keywords: Musculoskeletal system -- Diseases -- Nursing -- Handbooks, manuals, etc